2015
DOI: 10.1038/cr.2015.142
|View full text |Cite
|
Sign up to set email alerts
|

Pluripotent stem cells induced from mouse neural stem cells and small intestinal epithelial cells by small molecule compounds

Abstract: Recently, we reported a chemical approach to generate pluripotent stem cells from mouse fibroblasts. However, whether chemically induced pluripotent stem cells (CiPSCs) can be derived from other cell types remains to be demonstrated. Here, using lineage tracing, we first verify the generation of CiPSCs from fibroblasts. Next, we demonstrate that neural stem cells (NSCs) from the ectoderm and small intestinal epithelial cells (IECs) from the endoderm can be chemically reprogrammed into pluripotent stem cells. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
55
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 44 publications
5
55
0
Order By: Relevance
“…We previously demonstrated that, in contrast to OSKMinduced reprogramming, the first cornerstone of chemical reprogramming is the formation of plastic XEN-like cells marked by Gata4, Gata6, and Sox17, which resemble the extraembryonic endoderm (XEN) cells of the blastocyst at the preimplantation stage in terms of transcriptome, developmental ability, and reprogramming potential Ye et al, 2016;Zhao et al, 2015Zhao et al, , 2016. Recently, our findings were also confirmed by other groups (Cao et al, 2018;Ping et al, 2018) using a similar small molecule cocktail that targets the same pathways identified by our group.…”
Section: Introductionmentioning
confidence: 99%
“…We previously demonstrated that, in contrast to OSKMinduced reprogramming, the first cornerstone of chemical reprogramming is the formation of plastic XEN-like cells marked by Gata4, Gata6, and Sox17, which resemble the extraembryonic endoderm (XEN) cells of the blastocyst at the preimplantation stage in terms of transcriptome, developmental ability, and reprogramming potential Ye et al, 2016;Zhao et al, 2015Zhao et al, , 2016. Recently, our findings were also confirmed by other groups (Cao et al, 2018;Ping et al, 2018) using a similar small molecule cocktail that targets the same pathways identified by our group.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to mesoderm‐origin fibroblasts, neural stem cells originating from the ectoderm and intestinal epithelial cells originating from the endoderm can also be reprogrammed to pluripotency by the fine‐tuning of the small‐molecule cocktail . Notably, through similar gene expression analysis, genetic approaches and fluorescence‐activated cell sorting (FACS) experiments carried out in fibroblasts, we found that, although chemical reprogramming processes were initiated from cells of different germ layers, they underwent the same XEN‐like intermediate state during the induction of CiPSCs, implying the generality of the XEN‐like state during chemical reprogramming towards pluripotency …”
Section: Unique Route Towards Pluripotency During Chemical Reprogrammingmentioning
confidence: 78%
“…Although the use of direct protein mediated method could completely avoid this problem, the reprogramming efficiency was very low (Kim et al, ), so there was not much practical value. Currently, induced pluripotent stem cells (CiPSC) could be successfully reprogrammed by small‐molecule compounds from mouse somatic cells which had higher reprogramming efficiency and no exogenous genes integration (Hou et al, ; Kang et al, ; Yang et al, ; Ye et al, ). It could be the most ideal method for iPSCs generation.…”
Section: Introductionmentioning
confidence: 99%